Government support schemes during the Covid-19 pandemic have had a dampening effect on corporate credit risk - Ida Nervik Hjelseth; Haakon Solheim; Bjørn Helge Vatne (Norges Bank, 2021)
After the Covid-19 pandemic broke out, the authorities have introduced a number of measures aimed at the business sector. Support has largely been given to the sectors hardest hit by the pandemic and measures to contain it. A considerable share of banks' loan customers in these sectors have received support from one or more of these schemes. This has likely had a dampening effect on banks' credit loss risk.
hdl:11250/2755871
Keywords: 330; Covid-19; coronavirus; pandemic; support schemes; support measures; business sector; credit risk; financial stability